Regulation the reaction intermediates in methanation reactions via modification of nickel catalysts with strong base. (1st February 2019) - Zhang, Zhanming; Hu, Xun; Wang, Yi; Hu, Song; Xiang, Jun; Li, Cuncheng; Chen, Guozhu; Liu, Qing; Wei, Tao; Dong, Dehua
Graphical abstract: Highlights: KOH led to collapse of porous structure of alumina and aggregation of nickel. KOH addition to alumina introduced abundant weak, medium and strong basic sites. Formate intermediate formed over KOH/Al2 O3, while carbonates formed over Al2 O3 . Formate strongly absorbed on Ni-KOH/Al2 O3, leading to low activity for methanation. Ni-KOH/Al2 O3 promoted CO formation in steam reforming via promoting RWGS reaction. Abstract: In this study, strong basic sites were introduced into Ni/Al2 O3 catalysts via modification of the catalysts with the strong base like KOH. Effects of the basic sties on physiochemical properties of the catalysts and the reaction intermediates formed in methanation and reverse water gas shift reaction (RWGS) were investigated. The KOH added to the catalyst reacted with alumina, leading to the collapse of the porous structure, the decreased surface area and the aggregation of metallic nickel. The addition of KOH also introduced abundant weak, medium and strong basic sites, which helped to absorb/activate CO2 and further converted CO2 to CO through RWGS reaction via a formate intermediate formed. In the absence of KOH, carbonates were the main intermediates, decomposition of which to CO was relatively difficult. The in-situ DRIFTS study showed that the formate intermediates strongly absorbed on surface of Ni-KOH/Al2 O3 catalyst, preventing the further hydrogenation of CO intermediates to CH4 . However, the catalyst had high activity for the RWGS reaction to form CO. CO is a major by-product in steam reforming reactions. The superior activity of Ni-KOH/Al2 O3 for RWGS reaction contributed to CO formation when the catalyst was applied in steam reforming reactions.